Social responsabilty and environment dimension of small and medium entreprises in Algeria - Benissad, Adra (Journal of Human Sciences, 2021)
The social responsibility and environmental of small and medium enterprises and it's role in achieving sustainable development on the grounds that a modern concept and has become an important criterion for the success of enterprises it also achieves the level of weal being for the best society as it can add new economic value. The relationship between environment and economic development has known a prominent development, where his vision changed a conflict between them, Especially by the third world countries that were focusing all attention on advancing economic growth, at the expense of preserving the environment, to adopt a clear policy by motivating and supporting institutions that pay attention to social responsibility especially small and medium enterprises.